2023
DOI: 10.1002/acp.4036
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal position of low‐frequency words across line boundaries? An eye movement investigation

Abstract: When displaying text on a page or a screen, only a finite number of characters can be presented on a single line. If the text exceeds that finite value, then text wrapping occurs. Often this process results in longer, more difficult to process words being positioned at the start of a line. We conducted an eye movement study to examine how this artefact of text wrapping affects passage reading. This allowed us to answer the question: should word difficulty be used when determining line breaks? Thirty-nine parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
2
1
0
Order By: Relevance
“…Our results demonstrated that the way in which the text was presented did not result in global differences in reading efficiency and effectiveness (e.g., reading speed and comprehension accuracy), and effects were confined to return-sweep eye movement behavior (e.g., return-sweep and corrective saccades). Overall, our results are similar to those reported in a recent study that examined whether typesetting factors across line boundaries influence the reading of multi-line text in English (Parker et al, 2023 ). In their study, the position of low-frequency words across line boundaries (either at the start or the end of a line) had little impact on global reading performance (i.e., reading time and comprehension) but did have robust effects on local eye movements (e.g., return-sweeps).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrated that the way in which the text was presented did not result in global differences in reading efficiency and effectiveness (e.g., reading speed and comprehension accuracy), and effects were confined to return-sweep eye movement behavior (e.g., return-sweep and corrective saccades). Overall, our results are similar to those reported in a recent study that examined whether typesetting factors across line boundaries influence the reading of multi-line text in English (Parker et al, 2023 ). In their study, the position of low-frequency words across line boundaries (either at the start or the end of a line) had little impact on global reading performance (i.e., reading time and comprehension) but did have robust effects on local eye movements (e.g., return-sweeps).…”
Section: Discussionsupporting
confidence: 91%
“…Compared to intra-line fixations (223 ms), line-final fixations were shorter (206 ms), and accurate line-initial fixations were longer (235 ms). These results are consistent with those observed in alphabetic languages (e.g., Abrams & Zuber, 1972 ; Kuperman et al, 2010 ; Parker & Slattery, 2019 ; Parker et al, 2017 , 2020 , 2023 ). Assuming that these results reflect visual and cognitive processes at mid-line, line-final and line-initial positions and given that the fundamental format characteristics of text across alphabetic and character-based languages are comparable (horizontal text lines read from left to right), the consistency of effects across orthographies is perhaps not surprising.…”
Section: Discussionsupporting
confidence: 91%
“…The return-sweep planning account is, however, difficult to reconcile with findings from the current study as frequency and predictability effects emerge for line-final words, indicating that fixations on these words are being terminated based on lexical properties of the line-final word. The observation that word-level properties influence reading times on line-final words is not novel to this study Parker et al (2023). reported longer line-final fixation durations when low-frequency targets are positioned at the end of the line compared to a condition where low-frequency words are positioned at the start of a line.…”
mentioning
confidence: 65%
“…Finally, where-decisions have a strong impact at the end and beginning of a text line, as there is a large return sweep to be made from one line to the next. These are likely to affect the gaze duration of the first and last word of a text line and therefore it is common to remove these words from eye movement analyses unless one is interested in the return sweep itself (Parker et al, 2023;Slattery & Vasilev, 2019).…”
Section: Where Decisions Versus When Decisionsmentioning
confidence: 99%